How Iran Overrides IAEA to Examine Iran's Nuclear Energy Development - Sihotang, Widya S. R. (Journal of International Relations on Energy Affairs, 2022)
In human life, weapons of mass destruction pose a threat to all. Since the era of war has ended, the international world has no longer felt the presence of weapons of mass destruction. The research question found by the author in this article is Iran's efforts to deal with the IAEA which implements a unilateral policy to conduct inspections of Iran's nuclear energy. In addition, the author also limits the discussion to only the efforts made by Iran in rejecting the IAEA's actions to examine nuclear development in Iran. Before discussing these points, the author will provide a discussion of the reasons why the IAEA wants to examine Iran's nuclear development first. With the limitations of this research, the author can describe the discussion specifically and get good results. Neoliberal Institutionalism as one of the major theories of International Relations is the main point of view used by the author to analyze the formulation of the problem. Basically, Iran did not accept the examination submitted by the IAEA because Iran found the fact that the IAEA allegedly leaked some Iranian nuclear secrets so that Iran had lost confidence in the IAEA.